Chinese Political Elites in the Context of Chinese Political Thought and Political History - Keskin, Tuğrul (Cappadocia Journal of Area Studies, 2024)
The book Chinese Political Elites in the Context of Chinese Political Thought and Political History by Can Ulusoy offers an in-depth examination of China’s political elites, focusing on the historical and intellectual frameworks that shaped their actions and ideologies from 1840 to 1978. By drawing comparisons to similar processes in Turkish political history, Ulusoy seeks to understand China’s modern political developments. The book provides a comprehensive study of the evolution of political elites in China, spanning from the late Qing Dynasty to the early years of Deng Xiaoping’s rule, covering over a century of political transformations, ideological shifts, and elite maneuvering within the broader framework of Chinese modernization. Structured across multiple sections, the book explores various periods and transitions in China’s political history. It starts by examining traditional Chinese elites before 1840, emphasizing the impact of Confucianism, meritocracy, and the patrimonial imperial system. The text then addresses the challenges posed by the Opium Wars and increased interactions with Western powers, which led to reformist movements and the rise of new political elites. The study delves into the evolution of China’s elite system through significant historical events such as the Taiping Rebellion, the Self-Strengthening Movement, the Hundred Days’ Reform, and the Xinhai Revolution. It highlights the transition from traditional to modern political structures, focusing on key figures like Sun Yat-sen, Kang Youwei, and Liang Qichao. The book further examines the transformation of political elites under the Chinese Communist Party (CCP), including Mao Zedong’s dialectical thinking, the Cultural Revolution, and factional conflicts within the CCP. It also explores the strategies and ideologies that shaped the political environment after 1949, with distinct periods marked by the policies of Mao and Deng Xiaoping. Ulusoy emphasizes the resilience and adaptability of China’s political elites, drawing parallels with similar movements in Turkish political history, such as the Young Turks and the Kemalist revolution. This comparative approach offers insights into the broader implications of modernization and elite politics within a global context. One of the book’s strengths is its meticulous historical research, which provides a nuanced understanding of how traditional Chinese political thought, particularly Confucianism, continued to influence the political landscape even during periods of reform and revolution. By analyzing <img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAa4AAAABCAYAAACGyEoVAAAAAXNSR0IArs4c6QAAAHhlWElmTU0AKgAAAAgABAEaAAUAAAABAAAAPgEbAAUAAAABAAAARgEoAAMAAAABAAIAAIdpAAQAAAABAAAATgAAAAAABH7/AAALEgAEfv8AAAsSAAOgAQADAAAAAQABAACgAgAEAAAAAQAAAa6gAwAEAAAAAQAAAAEAAAAAgp4itwAAAAlwSFlzAAAP/QAAD/0BH2+0RwAAABtJREFUOBFjYBgFoyEwGgKjITAaAqMhMIRCAAAGuQABzqi/TQAAAABJRU5ErkJggg==" alt="page1image64482480" width="429.600000" height="0.480000"> <img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAOwAAAABCAYAAADdCUJIAAAAAXNSR0IArs4c6QAAAHhlWElmTU0AKgAAAAgABAEaAAUAAAABAAAAPgEbAAUAAAABAAAARgEoAAMAAAABAAIAAIdpAAQAAAABAAAATgAAAAAABNSXAAAL4QAE1JcAAAvhAAOgAQADAAAAAQABAACgAgAEAAAAAQAAAOygAwAEAAAAAQAAAAEAAAAA1VVA/wAAAAlwSFlzAAAQAgAAEAIB7mPqkwAAABNJREFUKBVjYBgFoyEwGgJDJgQAA7EAAVM3h2MAAAAASUVORK5CYII=" alt="page1image64482272" width="235.200000" height="0.480000"><img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAa4AAAABCAYAAACGyEoVAAAAAXNSR0IArs4c6QAAAHhlWElmTU0AKgAAAAgABAEaAAUAAAABAAAAPgEbAAUAAAABAAAARgEoAAMAAAABAAIAAIdpAAQAAAABAAAATgAAAAAABH7/AAALEgAEfv8AAAsSAAOgAQADAAAAAQABAACgAgAEAAAAAQAAAa6gAwAEAAAAAQAAAAEAAAAAgp4itwAAAAlwSFlzAAAP/QAAD/0BH2+0RwAAABtJREFUOBFjYBgFoyEwGgKjITAaAqMhMIRCAAAGuQABzqi/TQAAAABJRU5ErkJggg==" alt="page1image64482064" width="429.600000" height="0.480000"> <img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAOwAAAABCAYAAADdCUJIAAAAAXNSR0IArs4c6QAAAHhlWElmTU0AKgAAAAgABAEaAAUAAAABAAAAPgEbAAUAAAABAAAARgEoAAMAAAABAAIAAIdpAAQAAAABAAAATgAAAAAABNSXAAAL4QAE1JcAAAvhAAOgAQADAAAAAQABAACgAgAEAAAAAQAAAOygAwAEAAAAAQAAAAEAAAAA1VVA/wAAAAlwSFlzAAAQAgAAEAIB7mPqkwAAABNJREFUKBVjYBgFoyEwGgJDJgQAA7EAAVM3h2MAAAAASUVORK5CYII=" alt="page1image64481856" width="235.200000" height="0.480000"> 1 key moments like the Self-Strengthening Movement, the 1911 Revolution, and the Cultural Revolution, Ulusoy vividly portrays the conflicts, strategies, and ideologies that shaped the political elite’s decisions and survival. A major contribution of the work is its comparative analysis between Chinese and Turkish political modernizations. The parallels drawn between the roles of elites in these contexts offer fresh insights, suggesting that both nations, while under external pressure, had to navigate the balance between tradition and modernity. The discussion of elite theory and "elite circulation" adds depth, helping readers understand how certain groups maintained or shifted power across different regimes. The book is comprehensive, providing a detailed historical analysis supported by a wide range of sources. Its comparative approach to Turkish modernization adds a unique perspective, revealing common patterns in elite behavior during political transformation. Ulusoy effectively argues that both nations navigated their modernization through complex interactions with external powers, adapting traditional frameworks to address new challenges. However, the text sometimes leans towards overgeneralization, especially in comparing Chinese and Turkish political elites. While the parallels are compelling, the historical and cultural contexts differ greatly, which can occasionally weaken the effectiveness of direct comparisons. Additionally, the dense historical detail may be challenging for readers unfamiliar with Chinese history, making it harder to follow the narrative. Overall, the book succeeds in providing a detailed understanding of China’s political elites and their roles across different eras, making it a valuable resource for students of international relations and political history. The comparative angle adds to its academic appeal, though a more nuanced approach to the differences between Chinese and Turkish political contexts could enhance the analysis. Despite its depth, the book’s dense historical detail and broad scope can feel overwhelming at times. Readers unfamiliar with Chinese history might struggle with the narrative, especially when it delves into specific figures and events without much background. The comparative approach, while innovative, sometimes overemphasizes similarities between Chinese and Turkish contexts, occasionally glossing over critical differences in cultural, historical, and geopolitical realities. A clearer delineation of these differences could have strengthened the analysis, offering a more precise picture of why certain strategies succeeded in one setting but not the other. In conclusion, Chinese Political Elites in the Context of Chinese Political Thought and Political History is a valuable resource for scholars of political history and international relations. It offers a detailed account of how China’s political elites adapted to immense internal and external pressures over time. The book’s comparative analysis adds a unique layer, encouraging readers to think about modernization and elite politics in a global context. While some areas could benefit from a more refined focus, the book remains an insightful and thought-provoking exploration of Chinese political thought and history.